Generation of verbal stems in derivationally rich language - Šojat, Krešimir; Tadić, Marko; Mikelić Preradović, Nives (2012)
The paper presents a procedure for generating prefixed verbs in Croatian comprising combinations of one, two or three prefixes. The result of this generation process is a pool of derivationally valid prefixed verbs, although not necessarily occuring in corpora. The statistics of occurences of generated verbs in Croatian National Corpus has been calculated. Further usage of such language resource with generated potential verbs is also suggested, namely, enrichment of Croatian Morphological Lexicon, Croatian Wordnet and CROVALLEX.
Projekt MZOS
Projekt MZOS
ENG